2023
DOI: 10.1093/ehjqcco/qcad011
|View full text |Cite
|
Sign up to set email alerts
|

A hidden problem: peripheral artery disease in women

Abstract: Peripheral artery disease (PAD) has a huge social and economic burden and is an important contributor to the global health burden. Sex differences in PAD are apparent, with recent data suggesting equal if not greater prevalence in women, and women having worse clinical outcomes. Why this occurs is not clear. To identify underlying reasons for gender inequalities in PAD, we executed a deeper exploration through a social constructive perspective. A scoping review was conducted using the World Health Organization… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 98 publications
1
14
0
Order By: Relevance
“…Differences in the presentations of ALI as well as how resilient one is to the disease and treatment might also explain the seen difference. It is also important to recognize that, as identified in a recent study on PAD, several variables, including societal factors, are rarely explored as potential factors in sex‐based differences in an outcome 17 . Societal factors were not explored in the present study.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Differences in the presentations of ALI as well as how resilient one is to the disease and treatment might also explain the seen difference. It is also important to recognize that, as identified in a recent study on PAD, several variables, including societal factors, are rarely explored as potential factors in sex‐based differences in an outcome 17 . Societal factors were not explored in the present study.…”
Section: Discussionmentioning
confidence: 90%
“…It is also important to recognize that, as identified in a recent study on PAD, several variables, including societal factors, are rarely explored as potential factors in sexbased differences in an outcome. 17 Societal factors were not explored in the present study. The absence of difference in outcomes between sexes might have been caused by an element of selection bias in only including those undergoing surgical or endovascular revascularizations.…”
Section: Discussionmentioning
confidence: 94%
“…Differences in sex hormones may also affect arterial compliance, with post-menopausal females having increased arterial stiffness compared to males [13], a finding that is further exaggerated in conditions such as metabolic syndrome [14]. Arterial stiffness contributes to the increased prevalence of hypertension in women [15], and hypertension is a risk factor for PAD [16]. These differences in the biomechanical properties of arteries may affect the sex-dependent outcomes of PAD treatment.…”
Section: Biomechanical Considerationsmentioning
confidence: 99%
“…The causes behind this are multifactorial and underpinned by a complex interplay of variables at a micro-(biology and environmental risk factors), meso-(education and employment), and macrolevel (women's roles in society). 2 Within cardiovascular surgery, women have been shown regularly to have poorer outcomes; notably after coronary artery surgery and aortic aneurysm repair. 3,4 Previous meta-analysis investigating gender differences in vascular surgery reported that women had an equal if not higher prevalence of peripheral arterial disease (PAD), more severe disease at presentation and often have poorer outcomes.…”
mentioning
confidence: 99%
“…Unequal outcomes based on gender are reported widely in healthcare and often described as the gender gap. The causes behind this are multifactorial and underpinned by a complex interplay of variables at a micro‐ (biology and environmental risk factors), meso‐ (education and employment), and macrolevel (women's roles in society) 2 . Within cardiovascular surgery, women have been shown regularly to have poorer outcomes; notably after coronary artery surgery and aortic aneurysm repair 3,4 .…”
mentioning
confidence: 99%